PHYSIOLOGICAL AND AGRONOMIC RESPONSE OF CANOLA VARIETIES TO DROUGHT STRESS - J. Din; S. U. Khan; I. Ali; A. R. Gurmani (Journal of Animal and Plant Sciences, 2011)
The drought tolerance of canola cultivars viz., Shirale, Oscar, Con-II, Rainbow and 19H was investigated after exposure to drought stress at various growth stages in a pot experiment. Water stress was imposed at flowering and pod filling growth stages. Data of various physiological (leaf chlorophyll a & b, proline and protein contents) and agronomic attributes (number of pods/plant, seeds/pods, grain yield/plant) was recorded. The data revealed significant differences among the various canola genotypes for leaf chlorophyll a, b and proline accumulation. The chlorophyll a & b content of all the Napus genotypes declined due to drought stress at both the growth stages. Genotypes Rainbow showed least reduction (12%) in chlorophyll content during the flower initiation and pod filling stage. There were significant increases in osmosis-regulating substance proline under water stress. Rainbow accumulated highest proline. Drought treatment at different growth stages reduced grain yield significantly. Greater reduction in grain yield was observed when stress was imposed at flowering. Average yield was found greater in Rainbow and least in Oscar. The better osmoregulation ability under drought stress conditions proves Rainbow as drought tolerant cultivar. The findings of present research investigation suggested for growing of Rainbow in the areas of water scarcity to obtain economic yield.
Keywords: Canola; Brassica napus; drought; growth stages; chlorophyll; proline.